Rancang Bangun Alat Ukur Indeks Masa Tubuh Untuk Deteksi Diabetes Mellitus Tipe 2 - Arsianti, Rika Wahyuni; Alexander, Arif; Mulyadi, Mulyadi; Raudah, Raudah (J-Eltrik, 2019)
Type 2 diabetes mellitus is closely related to Body Mass Index. Type 2 diabetes mellitus is very influential on the quality of life of patients and requires substantial health costs. The prevalence of this disease is increasing every year due to changes in lifestyle behavior. Diabetes Mellitus can be prevented, delayed by controlling risk factors. One of the risk factors for diabetes mellitus type II is a high body mass index. The purpose of this research is designed prototype of Body Mass Index. This device consists of load cell sensors and ultrasonic sensors used to measure body weight and height. The accuracy of Body Mass Index Device is 98.5%. So this can be proposed as tools for measuring Body Mass Index. The number of subject in this research is 17. The result shows that 29.4% is categorized Body Mass Index with risk of type 2 diabetes mellitus.